IbM Pelatihan Tata Kelola Keuangan bagi UMKM Anggota Kelompok Usaha untuk Meningkatkan Kinerja Keuangan - Eliana; Rusman (AJAD : Jurnal Pengabdian kepada Masyarakat, 2021)
In the Indonesian economy, Micro, Small, and Medium Enterprises (MSMEs) are the business groups that have the largest number. In addition, this group is proven to be resistant to various shocks of economic crisis. So it is imperative to strengthen groups of micro, small and medium enterprises that involve many groups. The criteria for businesses that are included in Micro, Small, and Medium Enterprises have been regulated in a legal umbrella based on law. The development of the number of MSMEs from year to year is increasing. The development of MSMEs can only be seen in terms of numbers. In general, especially in the financial aspect, only a few MSMEs have experienced developments in terms of their financial performance. This is inseparable from the unconsciousness of MSME players of the importance of corporate financial management. The training program offered is in the form of simple accounting training for MSMEs. The accounting taught is simple accounting that is adjusted to the conditions in MSMEs but does not deviate from existing standards and regulations. This training is intended for MSME players who are members of the Delima District Business Group. With this training, it is hoped that MSME players will be able to know the development of the company and be able to take advantage of accounting to support the progress of their MSMEs. Based on the description above, basically, the community service program through service activities is divided into three activities, namely by using the lecture, tutorial, and discussion method and followed by the Delima District Business Group of 10 people.